Edukasi Pemanfaatan Teknologi Informasi dalam Bidang Pertanian di SMK Lentera Harapan - Prya Artha Widjaja; Simon P. Barus; Ary Budi Warsito (Jurnal Pengabdian Masyarakat Bestari, 2022)
Information technology has many benefits in everyday life. However, the use of information technology in agriculture in Indonesia still very lacking. This community service aim is to introduce the use of information technology in agriculture to students. This education is carried out in the form of seminar which was held on 15 March 2022 at SMK Lentera Harapan. It is hoped that students will get better information about the use of information technology in agriculture. We hope agriculture in Indonesia can grow using technology